Investigating the neurodevelopmental mediators of aggression in children with a history of child maltreatment:An exploratory field study. Issue 6 (18th August 2017) - Dileo, J. F.; Brewer, W.; Northam, E.; Yucel, M.; Anderson, V.
ABSTRACT: Maltreatment of children is a chronic community problem that increases the risk of future aggression. Despite several decades of research highlighting this relationship, few studies have explored the potential neuropsychological deficits that are likely to mediate it. This exploratory study aimed to examine how child maltreatment may be associated with aggression via impairment in the developing prefrontal-limbic-autonomic pathways that are implicated in neuropsychological models of aggression. Furthermore, it aimed to investigate the relationship between child maltreatment and both reactive and proactive aggression subtypes. To investigate this non-invasively in an at-risk population, children with a documented protective care history ( n = 20) and a community control group (n = 30), aged between 6 and 12 years, were compared on measures of cardiovascular functioning, affect regulation and cognitive functioning aligned with this neuropsychological model. Whilst no group differences were found on cardiovascular functioning (i.e., resting heart rate, heart rate reactivity, heart rate variability), the protective care group performed significantly worse on measures of affect regulation and cognitive functioning (i.e., global intelligence, executive functioning, smell identification and social cognition). The relationship between child maltreatment and aggression was mediated by executive dysfunction and affect dysregulation but not global IQ, social cognition or olfactory identification. The results suggest that interventions targeting aggression in maltreated children will benefit from clinical assessment and psychological strategies that address the executive dysfunction and affect dysregulation that has been associated with this clinical outcome.